Analytical and Numerical Analysis of the De Haller Criterion for Low-Pressure Axial Fans - Fritsche, Manuel; Epple, Philipp; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2023)
During the design process of low-pressure axial fans, load criteria are often applied to minimize losses and obtain optimal machines. Particularly in the case of decelerated flows, such as in a blade channel of an axial fan, the flow tends to detach and form vortices due to the positive pressure gradient. Exactly 70 years ago in 1953, based on experiments on a linear blade cascade in a wind tunnel, De Haller suggested limiting the velocity reduction between blade outlet and blade inlet to a ratio of 0.75. This De Haller criterion was analyzed in more detail in the present study. The De Haller criterion is examined on the basis of 16 different three-dimensional analytical impeller designs considering the radial equilibrium with different blade work distributions. Due to the three-dimensional approach in the radial and axial direction on several annular surfaces, it is possible to determine the existing flow field analytically. Due to the variation of the blade work distribution, the impeller is loaded differently, which leads to a change in the flow velocities and thus in the velocity reduction between blade inlet and outlet. The De Haller number can thus be examined using different blade work distributions. These analytical designs have been simulated using numerical flow simulation methods (Computational Fluid Dynamics - CFD). The three-dimensional CFD model was modelled with ANSYS Workbench 2022R2 and the RANS equations were solved with ANSYS CFX, after performing a detailed grid independence study based on the Richardson extrapolation. From the simulated CFD model, the velocities on the corresponding ring surfaces were evaluated and the associated De Haller number was determined. Two criteria were applied in order to quantify the flow detachment in order to compare the CFD results with the De Haller criteria. The first one is the flow blockage percentage, which indicates how much of the flow is detached and the second one is the wall shear stress on the blade surface, which indicates how well the flow is attached to the blades. Finally, the analytical and the numerical results are compared and the respective De Haller numbers are analyzed. There is a systematic deviation between the analytical design and the numerical simulation. The De Haller numbers of the numerical simulation are always higher than those of the analytical design. This is due to the non-ideal flow deflection in the blade channel. The analytical results and the numerical CFD simulations are explained and presented in detail.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Axial Fan; CFD; DeHaller Criterion